Y= 0.26x+4.4*10^-4
Y= 0.26x+4.4*10,000
Y=0.26x+44,000
I'm not sure if you were only trying to simplify the problem, but I hope this helped
Answer:
Step-by-step explanation:
Use the formula Sum = (a + L)*n/2
The tricky part is n. That's the number of terms between 1 and 99 inclusive.
n = 99 -1 + 1 = 99
n = 99
a = 1
L = 99
Sum = (1 + 99)*99 / 2
Sum = (100)*99/2
Sum = 4950
Answer:
$130
Step-by-step explanation:
If Nathan already has $90 then you would add the amount of money collected after the 4 weeks. In each week he makes $10.
The equation would be $90+($10x4)= $X
Answer:
x-y=4
and
x+y=32 is <u>your</u><u> </u><u>equation</u>
<u>d</u><u>i</u><u>f</u><u>f</u><u>e</u><u>r</u><u>e</u><u>n</u><u>c</u><u>e</u><u> </u><u>o</u><u>f</u><u> </u><u>t</u><u>w</u><u>o</u><u> </u><u>n</u><u>u</u><u>m</u><u>b</u><u>e</u><u>r</u><u> </u><u>=</u><u>x-y</u><u> </u><u>is</u><u> </u><u>equal</u><u> </u><u>to</u><u> </u><u>4</u>
<u>s</u><u>u</u><u>m</u><u> </u><u>o</u><u>f</u><u> </u><u>t</u><u>w</u><u>o</u><u> </u><u>n</u><u>u</u><u>m</u><u>b</u><u>e</u><u>r</u><u>=</u><u>x</u><u>+</u><u>y</u><u> </u><u>i</u><u>s</u><u> </u><u>e</u><u>q</u><u>u</u><u>a</u><u>l</u><u> </u><u>t</u><u>o</u><u> </u><u>3</u><u>2</u>
<u>x</u><u>-</u><u>y</u><u>=</u><u>4</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>(</u><u>1</u><u>)</u>
<u>x</u><u>+</u><u>y</u><u>=</u><u>3</u><u>2</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>(</u><u>2</u><u>)</u>
<u>a</u><u>d</u><u>d</u><u>i</u><u>n</u><u>g</u><u> </u><u>equation</u><u> </u><u>1</u><u> </u><u>a</u><u>n</u><u>d</u><u> </u><u>2</u>
<u>x</u><u>-</u><u>y</u><u> </u><u>+</u><u>x</u><u>+</u><u>y</u><u>=</u><u>4</u><u>+</u><u>3</u><u>2</u>
<u>2</u><u>x</u><u>=</u><u>3</u><u>6</u>
<u>x</u><u>=</u><u>3</u><u>6</u><u>/</u><u>2</u><u>=</u><u>1</u><u>6</u><u>a</u><u>n</u><u>s</u><u>w</u><u>e</u><u>r</u>
<u>s</u><u>u</u><u>b</u><u>s</u><u>t</u><u>i</u><u>t</u><u>u</u><u>t</u><u>i</u><u>n</u><u>g</u><u> </u><u>value</u><u> </u><u>of</u><u> </u><u>y</u><u> </u><u>in</u><u> </u><u>equation</u><u> </u><u>1</u>
<u>1</u><u>6</u><u>-</u><u>y</u><u>=</u><u>4</u>
<u>1</u><u>6</u><u>-</u><u>4</u><u>=</u><u>y</u>
<u>y</u><u>=</u><u>1</u><u>2</u><u> </u><u>a</u><u>n</u><u>s</u><u>w</u><u>e</u><u>r</u>